Effect of internal and external corrugated surfaces on the characteristics of heat transfer and pressure drop in a concentric tube heat exchanger - Begag, Abdelaziz; Saim, Rachid; Abboudi, Said; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
The main aim of the present work is to analyze the improvement of heat transfer through the simultaneous use of concave and convex inner and outer corrugated tubes within a concentric mini-tube heat exchanger. The purpose was to conduct a numerical study of the thermo-hydraulic characteristics of a concentric mini-tube heat exchanger with V-shaped corrugations, while considering different cases. In addition, hot water and cold water were used as working fluids. The simulations were performed for a countercurrent configuration, with mass flow rates of hot water and cold water ranging between 0.04 and 0.2 kg/s. The inlet temperature of hot fluid was set at 40 ?C and that of cold fluid at 15 ?C. The finite volume method was used to solve the mathematical model that allowed obtaining the temperature distribution, the heat transfer rate, as well as the entropy generation. These parameters were evaluated for different arrangements of the corrugated tubes. The results obtained showed that corrugations lead to improvement in the heat transfer rate due to higher exchange surface. A better average Nusselt number was also obtained from the arrangement of concave corrugated tubes with a phase shift angle of 180?.
Keywords: Corrugated tube; Laminar; Forced convection; Concentric mini tube; Heat exchanger